1998
DOI: 10.1038/sj.gt.3300591
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation-specific enhancer activity in transduced keratinocytes: a model for epidermal gene therapy

Abstract: HaCaT cells, a spontaneously immortalised, nontumoriAfter skin grafting to athymic mice, transduced HaCaT cells genic keratinocyte line, were used as a more amenable differentiated to form a stratified epidermis that remained model than primary keratinocytes for ex vivo-mediated viable for at least 99 days in some mice. Factor IX in gene transfer. These cells were transduced with retroviral plasma of mice grafted with vectors containing the HPVvectors containing the factor IX cDNA under the control of 16 and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Studies, carried out by other workers, showed that a 2,200-bp fragment of the human K14 gene upstream has potential to direct transgene expression in an epidermal keratinocyte [3,31,32]. More related to the present study is the research carried out by Page and coworkers [6,26] that demonstrated the expression of the hFIX in keratinocytes under the control of CMV promoter in combination with an enhancer corresponding to K14 gene.…”
Section: Introductionmentioning
confidence: 47%
See 1 more Smart Citation
“…Studies, carried out by other workers, showed that a 2,200-bp fragment of the human K14 gene upstream has potential to direct transgene expression in an epidermal keratinocyte [3,31,32]. More related to the present study is the research carried out by Page and coworkers [6,26] that demonstrated the expression of the hFIX in keratinocytes under the control of CMV promoter in combination with an enhancer corresponding to K14 gene.…”
Section: Introductionmentioning
confidence: 47%
“…Similarly, a variety of cell lines such as Chinese hamster ovary, baby hamster kidney, and human embryonic kidney-293 have been studied for the production of recombinant hFIX [23][24][25]. Keratinocytes are well-characterized hosts and attractive bioreactors to produce factor IX, and use of viral promoters to express biologically active FIX in there have been reported by several groups [5,12,26,27]. For the keratinocyte specific expression of a protein, a keratinocyte-specific regulatory system is required.…”
Section: Introductionmentioning
confidence: 98%
“…Similar to prior viral studies with a promoter active in all epidermal layers, we found that the CMV promoter employed in the pLAMB3 plasmid sufficed to support correctly polarized laminin 5 protein expression. Thus, although vectors targeting epidermal regions using layer-specific promoters have been developed, 26 they have proven unnecessary for properly restored protein distribution in both the current study and in the other epidermal genodermatoses corrected in vivo to date. 2,[21][22][23] This finding points to a post-transcriptional process, potentially facilitated by physical interactions with other laminin 5 chains and corresponding ligands, such as a6b4 integrin and Type VII collagen, that may direct correct laminin b3 distribution.…”
Section: Discussionmentioning
confidence: 98%
“…However, in recent years, concerns over potential risks for the transmission of human blood born infectious agents have motivated the use of recombinant forms of therapeutics [12,13]. Considering its key role in coagulation and its corresponding medical applications, several researches have been focused on the molecular aspects of hFIX and its production in eukaryotic systems [1,2,[11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%